Approaches to empty container repositioning problems in the context of Eurasian intermodal transportation. (June 2019) - Kuzmicz, Katarzyna Anna; Pesch, Erwin
Highlights: In the study the problem of empty containers repositioning with the possible container movements is described. The analysis is performed through the prism of Eurasian intermodal transportation and the Chinese initiative One Belt One Road. Different approaches to reducing this problem are analysed with taking into consideration technical solutions and optimisation methods application. The substantial part of the paper is devoted to a literature review of empty container problem modelling. Abstract: Container transportation has become an important part of global transportation and it may gain a new potential in the light of the Chinese One Belt One Road (OBOR) initiative, known in Europe also as the New Silk Road. It involves development of transport corridors – rail and maritime, linking China with Europe and it can be anticipated that its development will cause considerable shifts in container transportation from a sea into a rail (intermodal) route. In the light of substantial trade imbalance between Europe and China the problem of empty container repositioning gains specific importance. The aim of this study is the analysis of models and a variety of solutions to empty container repositioning problems through the prism of Eurasian intermodal transportation.